الحمايـة القانونية لبطاقات الدفع الإلكترونية - شرون, حسينة; بن مشري, عبد الحليم (Revue jurisprudence; Vol 11 No 01 (2019): مجلة الاجتهاد القضائي, 2019)
Electronic payment methods have become very modern and they are developing significantly. The market has been swept to a great extent because of the e-commerce privileges of ease, security and other privileges. Over the past 15 years, shopping has changed to Internet and e-payment. The purpose of this paper is to examine the nature and types of legal protection of electronic means of payment and their control systems and related challenges. The research focused on addressing these issues through analysis and discussion by addressing the main problem that revolves around the most important forms of legal protection of electronic payment methods.